2016
DOI: 10.1111/bld.12178
|View full text |Cite
|
Sign up to set email alerts
|

‘Putting music on’: everyday leisure activities, choice‐making and person‐centred planning in a supported living scheme

Abstract: Accessible summary• Essential Lifestyle Plans are a good way for people with learning disabilities and their support workers to tell people about things they like to do, such as listening to music.• These plans also tell people about the things that they need, like what medicine they may need to take.• Sometimes it is not easy to put the things we like to do at home into these plans because there are lots of things we do every day.• People need to think carefully about how the things we choose to do at home ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…Previous studies have identified similar negative experiences in community housing services, which supports the relevance of our findings for an international audience (Fisher et al. 2016 ; Fullana, Pallisera, and Díaz-Garolera 2019 ; Hassan 2017 ; Krotofil, McPherson, and Killaspy 2018 ; Wilken et al. 2018 ).…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have identified similar negative experiences in community housing services, which supports the relevance of our findings for an international audience (Fisher et al. 2016 ; Fullana, Pallisera, and Díaz-Garolera 2019 ; Hassan 2017 ; Krotofil, McPherson, and Killaspy 2018 ; Wilken et al. 2018 ).…”
Section: Discussionsupporting
confidence: 90%
“…It is important to ensure that supports match the unique needs of the individual to enable the most meaningful and active involvement possible while providing protection from possible manipulation. Hassan (2016) found that choices being made by individuals diagnosed with I/DD may not be made with as much agency and control as it may seem to support staff without proper training and consideration of environmental factors. Participants may have enjoyed listening to music or watching television as leisure activities, but they were also mostly reliant on the staff to operate the devices and could not necessarily decide to participate in those activities without staff support.…”
Section: Communicationmentioning
confidence: 99%